2014
DOI: 10.1021/bi401517f
|View full text |Cite
|
Sign up to set email alerts
|

Functionality of the Three-Site Ferroxidase Center of Escherichia coli Bacterial Ferritin (EcFtnA)

Abstract: At least three ferritins are found in the bacterium Escherichia coli, the heme-containing bacterioferritin (EcBFR) and two non-heme bacterial ferritins (EcFtnA and EcFtnB). In addition to the conserved A- and B-sites of the diiron ferroxidase center, EcFtnA has a third iron-binding site (the C-site) of unknown function that is nearby the diiron site. In the present work, the complex chemistry of iron oxidation and deposition in EcFtnA has been further defined through a combination of oximetry, pH stat, stopped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 61 publications
(422 reference statements)
2
50
0
Order By: Relevance
“…Moreover, consistent with this speculation is our previous Mössbauer study of PfFtn, in which we found that the Mössbauer parameters of Fe(II) in site C before the addition of dioxygen are different than those after the addition of dioxygen (Table 1) 10. The importance of site C for efficient catalysis of Fe(II) oxidation has been reported for other ferritins namely Escherichia coli ferritin A 25, 26 and Desulfovibrio vulgaris Hildenborough ferritin 27.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, consistent with this speculation is our previous Mössbauer study of PfFtn, in which we found that the Mössbauer parameters of Fe(II) in site C before the addition of dioxygen are different than those after the addition of dioxygen (Table 1) 10. The importance of site C for efficient catalysis of Fe(II) oxidation has been reported for other ferritins namely Escherichia coli ferritin A 25, 26 and Desulfovibrio vulgaris Hildenborough ferritin 27.…”
Section: Discussionsupporting
confidence: 90%
“…An intermediate with visible absorbance between 500 and 800 nm and centered at a different wavelength in different ferritins 1,7,19,[28][29][30] has been reported during the catalysis of Fe(II) oxidation. For example the progress curves of this intermediate in HuHF (650 nm) and PfFtn (620 nm) are shown in Fig.…”
Section: Paper Molecular Biosystemsmentioning
confidence: 99%
“…However, all cells do use inorganic bio-mineralization to maintain near constant concentrations of essential trace metals via high affinity chelators and storage proteins for times of excess. One prominent example are the ferritins, a ubiquitous class of proteins found in all domains of life that play a crucial role in iron homeostasis212131415161718. Ferritins form shells composed of 24 monomers each, creating an inner cavity in order to store iron in a hydrated amorphous form of iron oxide similar to the mineral ferrihydrite.…”
mentioning
confidence: 99%